DEVELOPING A PURPOSIVE CHANGE MANAGEMENT FRAMEWORK TO FACILITATE HEALTHCARE INFORMATION SYSTEMS IMPLEMENTATION SUCCESS - (:unkn) unknown (My University, 2024)
Current project and change management models have largely proven ineffective in smoothing transition and improving adoption of electronic health records (EHR). A holistic systems-thinking approach is required to improve the success of EHR implementations. Many of the widely used change management models appear to be lacking, in particular, they are not actionable nor sufficient alone because the change management models lack inclusion of project management aspects, which is especially concerning for EHR implementations. Success in products meeting intended benefits as result of managing projects across their life cycle requires change management as a discipline, rather treating it as an activity. A systematic thorough review of recent literature provided understanding of change management challenges and gathered published data about its effect on healthcare information systems implementation resulting in poor project outcomes. A survey instrument collected data from healthcare professionals, informaticists, and project team leaders which provided a comprehensive understanding into how current change management efforts performed and what challenges or problems exist. An integrated mixed-methods analysis using this data resulted in strategic insight into the many organizational factors which influence an individuals’ attitude towards change, which are key indicators of the effectiveness of change efforts in the implementation of an EHR. Applying this information, a conceptual change management framework was designed using a structured framework development approach. Lastly, an appreciative inquiry exercise in problem-solving by engaging with organizational leaders and users, helped to improve the conceptual change management framework into its final design. Industry consistently supports that a careful and multi-disciplined approach to applying lessons-learned and comprehensive planning helps to drive successful EHR implementations. In response, a ‘best-of-breed’ change management framework design was proposed, which offers an actionable way forward and includes mechanisms for transitioning internal and external stakeholders from the current-state to the desired future-state. The proposed change management framework links psychological and change management models with project management frameworks into a comprehensive solution; leveraging the natural flow of each into a logical design which maintains primary a focus on business needs and promotes ease of transition and end-user adoption.
Keywords: Health care management